Posthemispherectomy hydrocephalus: Results of a comprehensive, multiinstitutional review. (25th October 2012) - Lew, Sean M.; Matthews, Anne E.; Hartman, Adam L.; Haranhalli, Neil; on behalf of the Post‐Hemispherectomy Hydrocephalus Workgroup
Summary Purpose: Hemispherectomy surgery for medically intractable epilepsy is known to cause hydrocephalus in a subset of patients. Existing data regarding the incidence of, and risk factors for, developing posthemispherectomy hydrocephalus have been limited by the relatively small number of cases performed by any single center. Our goal was to better understand this phenomenon and to identify risk factors that may predispose patients to developing hydrocephalus after hemispherectomy surgery. Methods: Fifteen pediatric epilepsy centers participated in this study. A retrospective chart review was performed on all available patients who had hemispherectomy surgery. Data collected included surgical techniques, etiology of seizures, prior brain surgery, symptoms and signs of hydrocephalus, timing of shunt placement, and basic demographics. Key Findings: Data were collected from 736 patients who underwent hemispherectomy surgery between 1986 and 2011. Forty‐six patients had preexisting shunted hydrocephalus and were excluded from analysis, yielding 690 patients for this study. One hundred sixty‐two patients (23%) required hydrocephalus treatment. The timing of hydrocephalus ranged from the immediate postoperative period to 8.5 years after surgery, with 43 patients (27%) receiving shunts >90 days after surgery. Multivariate regression analysis revealed anatomic hemispherectomies (odds ratio [OR] 4.1, p < 0.0001) and previous brain surgery (OR 1.7, p = 0.04) as independent significant risk factors for developing hydrocephalus. There was a trend toward significance for the use of hemostatic agents (OR 2.2, p = 0.07) and the involvement of basal ganglia or thalamus in the resection (OR 2.2, p = 0.08) as risk factors. Significance: Hydrocephalus is a common sequela of hemispherectomy surgery. Surgical technique and prior brain surgery influence the occurrence of posthemispherectomy hydrocephalus. A significant portion of patients develop hydrocephalus on a delayed basis, indicating the need for long‐term surveillance.